The risk of hip and non-vertebral fractures in type 1 and type 2 diabetes: A systematic review and meta-analysis update - Vilaca, Tatiane; Schini, Marian; Harnan, Susan; Sutton, Anthea; Poku, Edith; Allen, Isabel E.; Cummings, Steven R.; Eastell, Richard (Bone (New York, N.Y.), 2020)
Diabetes is associated with increased fracture risk but we do not know what affects this risk. We investigated the risk of hip and non-vertebral fractures in diabetes and whether this risk was affected by age, gender, body mass index, diabetes type and duration, insulin use and diabetic complications. We selected a previously published review to be updated. MEDLINE, Embase and Cochrane databases were searched up to March 2020. We included observational studies with age and gender-adjusted risk of fractures in adults with diabetes compared to adults without diabetes. We extracted data from published reports that we summarised using random effects model. From the 3140 records identified, 49 were included, 42 in the hip fracture analysis, reporting data from 17,571,738 participants with 319,652 fractures and 17 in the non-vertebral fracture review, reporting data from 2,978,487 participants with 181,228 fractures. We found an increase in the risk of fracture in diabetes both for hip (RR 4.93, 3.06–7.95, in type 1 diabetes and RR1.33, 1.19–1.49, in type 2 diabetes) and for non-vertebral fractures (RR 1.92, 0.92–3.99, in type 1 and RR 1.19, 1,11–1.28 in type 2). At the hip, the risk was higher in the younger population in both type 1 and type 2 diabetes. In those with type 2 diabetes, longer diabetes duration and insulin use was associated with an increased risk. We did not investigate the effect of bone density, falls, anti-diabetic drugs and hypoglycemia. Diabetes is associated with an increase in both hip and non-vertebral fracture risk. •The risk of hip fractures was greater in T1D than T2D.•Hip fracture risk is higher in people younger than 65 years for both type 1 and type 2 diabetes.•In type 2 diabetes, insulin use and longer diabetes duration is associated with greater risk of hip fractures.